Gender differentials of contraceptive knowledge and use among youth – evidence from demographic and health survey data in selected African countries - Mkwananzi, Sibusiso (Frontiers in Global Women's Health, 2022)
Improving family planning demand and uptake havehas both social and economic benefits, including increasing education attainment, reducing poverty and increased participation in the labour force. Also, contraceptive use remains a key driver in Africa to facilitate demographic transition and the demographic dividend. However, numerous challenges have prevented the take uptake-up of contraception across the continent. This is more so the case among African youth that present the lowest levels of contraceptive use in sub-Saharan Africa. Therefore, the objective of this research was to examine gender differences in contraceptive use and knowledge of sexually active young people (15-–24 years) in sub-Saharan African countries. This study used data from nine countries in sub-Saharan Africa through the Demographic and Health Surveys (DHSs) of Benin, Democratic Republic of Congo, Lesotho, Namibia, Niger, Rwanda, Senegal, South Africa and Zimbabwe. Data analysis entailed frequency distributions and cross- tabulations to describe the gender- differentiated levels of contraceptive use and knowledge among youth. Additionally, logistic regression showed the gender-specific predictors of contraceptive use for African youth. Our findings present the gender-specific predictors of contraceptive use and will contribute to policy and programme formulation for African countries and organisations that promote contraceptive use.